2004
DOI: 10.1080/01140671.2004.9514277
|View full text |Cite
|
Sign up to set email alerts
|

Rockwool in horticulture, and its importance and sustainable use in New Zealand

Abstract: A brief history of the beginnings of the use of rockwool in horticulture in overseas countries, an outline of uses overseas of the current forms of water absorbent and water repellent horticultural rockwool, a summary of manufacturers of the product, a consideration of some of its advantages and disadvantages, and a listing of the crops grown in horticultural rockwool are given in this paper. An outline of the overseas experiences in both the disposal of and the sustainable reuse of horticultural rockwool is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 10 publications
0
31
0
5
Order By: Relevance
“…Proses pembuatan rockwool yang melibatkan suhu tinggi membuatnya steril dari mikroorganisme patogen, hama, ataupun benih gulma. Air juga mudah terlepas dari serat-serat rockwool sehingga struktur rockwool memberikan rasio air dan udara yang optimum bagi pertumbuhan tanaman (Bussell & McKennie, 2004). Rockwool bersifat inert secara biologis dan kimiawi sehingga penggunaannya tidak akan memodifikasi atau membatasi suplai nutrisi bagi tanaman.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Proses pembuatan rockwool yang melibatkan suhu tinggi membuatnya steril dari mikroorganisme patogen, hama, ataupun benih gulma. Air juga mudah terlepas dari serat-serat rockwool sehingga struktur rockwool memberikan rasio air dan udara yang optimum bagi pertumbuhan tanaman (Bussell & McKennie, 2004). Rockwool bersifat inert secara biologis dan kimiawi sehingga penggunaannya tidak akan memodifikasi atau membatasi suplai nutrisi bagi tanaman.…”
Section: Pendahuluanunclassified
“…Rockwool bersifat inert secara biologis dan kimiawi sehingga penggunaannya tidak akan memodifikasi atau membatasi suplai nutrisi bagi tanaman. Lebih dari 98% air dan unsur-unsur hara dapat diserap oleh tanaman dalam sistem hidroponik dengan rockwool sebagai media tanam (Bussell & McKennie, 2004). Meskipun demikian, penggunaan rockwool dianggap belum berkelanjutan, dan seratnya pernah diduga memicu kanker paru-paru (Drent et al, 2000;Bussell & McKennie, 2004).…”
Section: Pendahuluanunclassified
“…However, it is important to note that the disposal problem for mineral wool has led to criticism of its current usage. Some authors, such as Bussell and Mckennie [19], showed some options to reuse rockwool, but when analyzing the life cycle assessment of horticultural growing media, Quantis [20] reported that mineral wool has the highest negative impacts on human health. In addition, freight costs are relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…Some plants even survived without any fogging in GRW. One possible reason for this observed survival of plants is that both GRW and RWC have excellent water-holding and aeration characteristics [26]. Moreover, GRW has a higher number of large pores among particles that are more conducive to rooting than RWC, thus some plants even survived in the absence of fogging GRW.…”
Section: Discussionmentioning
confidence: 99%